Association Between Neutrophil–Lymphocyte Ratio and Frailty: The Chinese Longitudinal Healthy Longevity Survey - Xu, Weihao; Liang, Yuanfeng; Lin, Zhanyi (Frontiers in Medicine, 2022)
Background Inflammation has been reported to play an important role in frailty syndrome. The neutrophil–lymphocyte ratio (NLR) has recently emerged as an informative marker for systematic inflammation. However, few studies have examined the association between NLR and frailty. This study aims to examine the association between NLR and frailty in community-dwelling older adults. Methods Community-dwelling older adults aged ≥ 65 years in the 2011 (n = 2354) and 2014 (n = 2458) waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were included. Frailty status was determined using the 38-item frailty index (FI) and categorized into “robust” (FI ≤ 0.1), “pre-frail” (0.1 < FI ≤ 0.21), or “frail” (FI > 0.21). NLR was calculated using a derived formula: NLR = (white blood cell − lymphocyte)/lymphocyte. Results A total of 3267 participants were finally included. In cross-sectional analyses, participants with higher NLR levels had increased likelihood of frailty (the 3rd quartile: adjusted odds ratio [OR] = 1.29; 95% confidence interval [CI]: 1.02–1.63; the 4th quartile: OR = 1.59; 95% CI: 1.23–2.02) compared with those in the 1st quartile group. During the 3-year follow-up, 164 of the 1206 participants, robust or pre-frail at baseline, developed frailty, and 197 of the 562 participants, robust at baseline, developed pre-frailty or frailty. Among the robust and pre-frail participants in 2011, after multivariate adjustment, those in the 4th quartile group had a higher frailty incidence than those in the 1st quartile group (OR = 2.06; 95% CI: 1.18–3.59). Among the robust participants in 2011, those in the 4th quartile group also had a higher pre-frailty or frailty incidence than those in the 1st quartile group (OR = 1.95; 95% CI: 1.07–3.55). Conclusion Among community-dwelling older adults, higher NLR levels were found to be associated with increased odds of prevalent and incident frailty.